Prognostic value of lymphocyte count, NLR and PLR on admission for COVID-19 patients at Tishreen University Hospital in Lattakia - فراس حسين, (Latakia University Journal -Medical Sciences Series, 2023)
Background: Since December 2019, Coronavirus has been spreading widely until it became a fatal global pandemic. We’re currently in a great need to determine early and effective predictive biomarkers for the severity and mortality, in order to understand the pathophysiological mechanisms of the disease, and to find better treatment approaches. Object: Studying the relationship between lymphocyte count, neutrophil to lymphocyte ratio(NLR) and the platelet to lymphocyte ratio (PLR) and clinical and radiologic severity , mortality rate in patients with COVID-19 on admission. Methods: Prospective cohort study, Samples were collected from the COVID department of Tishreen University Hospital in Latakia from May 2020 to December 2020. Samples were sequentially included according to admission date based on the results of COVID-19 nasal swab test, characterization of demographic variables (age and gender), clinical and radiologic severity upon admission, in addition to the laboratory results. Patients' clinical progress was followed up during hospitalization, as well as their need for supportive oxygen (invasive and non-invasive mechanical ventilation) and the occurrence of complications during hospitalization. Finally, we listed the cases of recovery and death. Results: The sample included 284 patients. 194 males and 90 females. Patients aged between 27 and 92 years, with a mean age of 65. Each variable was studied in relation to clinical, radiologic severity and death. We found that lymphocytopenia on admission was associated with an increased clinical severity (P-value = 0.002) and a higher mortality (P-value = 0.02). A higher neutrophil to lymphocyte ratio was associated with an increased clinical and radiologic severity, and a higher mortality (P-value = 0.0001). As for the increase in the platelet to lymphocyte ratio, it was associated with a more severe illness; clinically (P-value = 0.0001) and radiologically (P-value = 0.0001), as well as a higher mortality (P-value = 0.006). Conclusion: Comprehensive laboratory tests must be performed for COVID patients upon admission; the most important of which are: WBC – Lumphocyte count – NLR – PLR. This helps to identify high risk patients in order to provide them with early intensive care, as they’re more likely to develop severe respiratory complications. Regular radiologic scanning (Chest CT with contrast – Doppler ultrasonography) should also be performed to detect these complications early and treat them appropriately.